Are You What You Eat? Healthy Behaviour and Risk Preferences - Miraldo,M; Galizzi,MM (B E JOURNAL OF ECONOMIC ANALYSIS & POLICY, 2017)
We elicit and estimate risk preferences for a pool of young adults in the UK, and explore their links with healthy eating and risky health behaviours. We construct the Healthy Eating Index (HEI) as an overall indicator of nutritional quality, and we use it to complement the body mass index BMI. While for females we find no significant association between the BMI and risk preferences, males with high BMI appear more risk-seeking. However, this association disappears when controlling for the quality of the diet. For males, the HEI is significantly associated with risk preferences. Males smoking status is not associated with risk preferences.